Formulation and characterization of orodispersible tablet of glimepiride - Ahmad AB Yosef Kinani; Hassanien Sagban Taghi (Wolters Kluwer Medknow Publications, 2022)
The present study is regarding, Glimepiride is one derivatives of sulfonyl urea used in the treatment of Type II DM which classified as class-II (BCS) of high permeability and low degree of solubility. The endeavor is to improve its solubility by solvent vaporization method to enhance the rate of dissolution of glimepiride. Soluplus (Polyvinyl caprolactampolyvinyl acetate-polyethylene glycol graft co-polymer) , PVP k40 (Polyvinylpyrrolidone) and PEG k5 are blended with the drug in various proportions (1:1,1:3) and prepared Soluplus1, Soluplus2, PEG1, PEG2, PVP1 and PVP2 as solid dispersion. The optimized formula of solid dispersion PVP1 is added to sodium starch glycolate and cross-carmellose. The disintegration profile will appear diminished in the drug release from the dosage form at a determined period of time. Differential scanning calorimetry appeared to a reduction in its crystallinity in solid dispersions. Scanning electron microscope and particle size analysis show a reduction in the drug particle size as solid dispersions. Fourier transform infrared spectroscopy does not show an interaction between them. Hence, that PVP1 batch will be considered from nine oral dissolving tablets dosage form. Finally, orally disintegrating tablets are estimated for various parameters; for instance, disintegration time, the content of the drug, wetting time, and in vitro release profile show a conventional result. The selected formula F6 shows a good result in disintegration time during 13-second and in-vitro drug release profile achieves 96% at the end of 40 minutes.